Transportna ekonomija - Božičnik, Stane (University of Maribor Press, 2020)
Transport Economics. The definition of transport and economics is given in order to clearly define what the transport economics is. Key macroeconomic categories, such as GDP, are explained. Transport as a system is presented from various political-economic systemic angles. The basics of market and market mechanism, as key for understanding the market-based economic mechanisms and phenomena are presented. Analytical tools for assessment of the competitive advantage of the company and selection / evaluation of market opportunities and strategies are highlighted. Knowledge of the markets and market mechanisms, mastering the marketing skills and understanding costs’ types, structure and dynamics, as well as calculation methods, break-even point, depreciation and pricing methods, is fundamental for management of the (transport) company. The management of the company must at the same time know, manage and coordinate both areas, the market (marketing) and the economics of the company in order to be successful. The selected methods for evaluation of investment projects and basics of business plans are presented too. The theory and practice of external costs calculation in transport and available market-based mechanisms for transport regulation, are presented in the last chapter.